Dynamic Characteristic Analysis of Asymmetric Helical Gear with a Small Number of Teeth based on LS-DYNA - Zhou Qi (Jixie chuandong)
The asymmetric helical gear with a small number of teeth as a new type gear has the advantages of small volume and strong bearing capacity,but the analysis of its dynamic characteristics especially research on the influence of elastic contact impact on the stability of gear transmission system caused by instantaneous normal relative velocity is less. Based on contact- impact dynamics equations,the finite element dynamic contact model of asymmetric helical gear with a small number of teeth is built,the dynamic tooth root bending stress and the dynamic transmission error are investigated under the condition of considering the effects of friction and damping,etc. The dynamic distribution of tooth root in a meshing period of the bending stress is described. The static and dynamic bending stress of tooth root in the whole meshing process of the helical gear pair is compared,and the influence of operating parameters on the bending strength is analyzed. Due to the elastic impact caused by instantaneous normal relative speed difference of gear contact point is analyzed. Taking the instantaneous impact process of the asymmetric helical gear pair with a small number of teeth as the research object,the different impact position（ tooth root,the pitch circle and tooth top） on impact force,impact stress and impact time under different speed are analyzed,and the impact stress of asymmetric helical gear and symmetric helical gear are analyzed and compared.